Genomic and in vitro pharmacodynamic analysis of rifampicin resistance in multidrug‐resistant canine Staphylococcus pseudintermedius isolates. Issue 3 (21st April 2021) - Hicks, Karly; Tan, Yongjun; Cao, Wenqi; Hathcock, Terri; Boothe, Dawn; Kennis, Robert; Zhang, Dapeng; Wang, Xu; White, Amelia
Abstract : Background: Antimicrobial resistance is a growing concern in canine Staphylococcus pseudintermedius dermatitis. Treatment with rifampicin (RFP) is considered only in meticillin‐resistant and multidrug‐resistant S. pseudintermedius (MDR‐MRSP). Hypothesis/Objectives: To determine an optimal RFP dosing for MDR‐MRSP treatment without induction of RFP resistance and identify causal mutations for antimicrobial resistance. Methods and materials: Time–kill assays were performed in a control isolate and three MDR‐MRSP isolates at six clinically relevant concentrations [32 to 1, 024 × MIC (the minimum inhibitory concentration)]. Whole‐genome resequencing and bioinformatic analysis were performed in the resistant strains developed in this assay. Results: The genomic analysis identified nine antimicrobial resistance genes (ARGs) in MDR‐MRSP isolates, which are responsible for resistance to seven classes of antibiotics. RFP activity against all four isolates was consistent with a time‐dependent and bacteriostatic response. RFP resistance was observed in six of the 28 time–kill assays, including concentrations 64 × MIC in MDR‐MRSP1 isolates at 24 h, 32 × MIC in MDR‐MRSP2 at 48 h, 32 × MIC in MDR‐MRSP3 at 48 h and 256 × MIC in MDR‐MRSP3 at 24 h. Genome‐wide mutation analyses in these RFP‐resistant strains discovered the causal mutations in the coding region of the rpoB gene. Conclusions and clinical relevance: A study has shown that 6 mg/kg per os results in plasma concentrations of 600–1, 000 × MIC of S. pseudintermedius . Based on our data, this dose should achieve the minimum MIC (×512) to prevent RFP resistance development; therefore, we recommend a minimum daily dose of 6 mg/kg for MDR‐MRSP pyoderma treatment when limited antibiotic options are available. Abstract : Background – Antimicrobial resistance is a growing concern in canine Staphylococcus pseudintermedius dermatitis. Treatment with rifampicin (RFP) is considered only in meticillin‐resistant and multidrug‐resistant S. pseudintermedius (MDR‐MRSP). Hypothesis/Objectives – To determine an optimal RFP dosing for MDR‐MRSP treatment without induction of RFP resistance and identify causal mutations for antimicrobial resistance. Conclusions and clinical relevance – A study has shown that 6 mg/kg per os results in plasma concentrations of 600–1, 000 × MIC of S. pseudintermedius . Based on our data, this dose should achieve the minimum MIC (×512) to prevent RFP resistance development; therefore, we recommend a minimum daily dose of 6 mg/kg for MDR‐MRSP pyoderma treatment when limited antibiotic options are available. Résumé: Contexte: Les résistances aux antibiotiques sont de plus en plus importantes pour les dermatites canines à Staphylococcus pseudintermedius . Le traitement à la rifampicine (RFP) est envisagé seulement pour les MDR‐MRSP ( S. pseudintermedius résistant à la méticilline et multi résistant). Hypothèses/Objectifs: Déterminer une dose optimale de RFP pour le traitement des MDR‐MRSP sans induire de résistance à RFP et identifier les mutations en cause pour la résistance antimicrobienne. Matériels et methods: Le temps d'élimination a été réalisé pour une souche contrôle et trois MDR‐MRSP à six concentrations cliniquement importantes [32 à 1, 024 × MIC (minimum inhibitory concentration)]. Le séquençage de tout le génome et l'analyse bio‐informatique ont été réalisés dans les souches résistantes développées dans cette étude. Résultats: Les analyses génomiques ont identifié neuf gènes de résistances antimicrobiennes (ARGs) dans les souches MDR‐MRSP, qui étaient responsable de résistance à sept classes d'antibiotiques. L'activité RFP contre les quatre souches était compatible avec une réponse bactériostatique et temps‐dépendante. La résistance à RFP a été observée pour six des 28 tests de temps d'élimination incluant les concentrations 64 x MIC des souches à MDR‐MRSP1 à 24 h, 32x MIC des MDR‐MRSP2 à 48h, 32 × MIC des MDR‐MRSP3 à 48 h et 256 × MIC des MDR‐MRSP3 à 24 h. Les analyses de mutation de génome dans ces souches résistantes à RFP ont découvert les mutations en cause dans la région codant pour le gène rpoB . Conclusions et importance Clinique: Une étude a montré que 6 mg/kg per os résultaient en des concentrations plasmatiques de 600‐1000 x MIC de S. pseudintermedius . Basé sur nos données, cette dose pourrait atteindre la MIC minimum (x512) pour prévenir le développement de résistances à RFP ; ainsi, nous recommandons une dose journalière minimum de 6 mg/kg pour les pyodermites MDR‐MRSP quand des options antibiotiques limitées sont disponibles. Resumen: Introducción: la resistencia a los antimicrobianos es una preocupación creciente en la dermatitis canina por Staphylococcus pseudintermedius . El tratamiento con rifampicina (RFP) se considera solo en S. pseudintermedius resistente a meticilina y resistente a múltiples fármacos (MDR‐MRSP). Hipótesis/Objetivos: determinar una dosis de RFP óptima para el tratamiento de MDR‐MRSP sin inducción de resistencia a RFP e identificar mutaciones causales de resistencia a los antimicrobianos. Materiales y métodos: Se realizaron ensayos de tiempo de eliminación en un aislado de control y tres aislados MDR‐MRSP a seis concentraciones clínicamente relevantes [32 a 1, 024 × MIC (la concentración inhibitoria mínima)]. La resecuenciación del genoma completo y el análisis bioinformático se realizaron en las cepas resistentes desarrolladas en este ensayo. Resultados: el análisis genómico identificó nueve genes de resistencia a los antimicrobianos (ARGs) en los aislados de MDR‐MRSP, que son responsables de la resistencia a siete clases de antibióticos. La actividad de RFP contra los cuatro aislamientos fue consistente con una respuesta bacteriostática dependiente del tiempo. Se observó resistencia a la RFP en seis de los 28 ensayos de eliminación temporal, incluidas concentraciones de 64 × MIC en aislados de MDR‐MRSP1 a las 24 h, 32 × MIC en MDR‐MRSP2 a las 48 h, 32 × MIC en MDR‐MRSP3 a las 48 h y 256 × MIC en MDR‐MRSP3 a las 24 h. Los análisis de mutaciones de todo el genoma en estas cepas resistentes a RFP descubrieron las mutaciones causales en la región codificante del gen rpoB. Conclusiones y relevancia clínica: un estudio ha demostrado que 6 mg/kg por vía oral dan como resultado concentraciones plasmáticas de 600‐1.000 × CMI de S. pseudintermedius . Según nuestros datos, esta dosis debería alcanzar la CMI mínima (× 512) para prevenir el desarrollo de resistencia a la RFP; por lo tanto, recomendamos una dosis diaria mínima de 6 mg/kg para el tratamiento de la pioderma causada por MDR‐MRSP cuando hay opciones limitadas de antibióticos disponibles. Zusammenfassung: Hintergrund: Die Antibiotika Resistenz gewinnt zunehmend an Bedeutung bei der Staphylococcus pseudintermedius Dermatitis des Hundes. Eine Behandlung mit Rifampicin (RFP) wird nur in Betracht gezogen, wenn es sich um einen Methicillin‐resistenten und multiresistenten S. pseudintermedius (MDR‐MRSP) handelt. Hypothese/Ziele: Es war das Ziel, eine optimale Dosierung von RFP zur MDR‐MRSP Behandlung ohne die Auslösung einer RFP Resistenz zu bestimmen und verursachende Mutationen der antimikrobiellen Resistenz zu identifizieren. Materialien und Methoden: Es wurden bei einem Kontrollisolat und bei drei MDR‐MRSP Isolaten Time‐kill Assays bei sechs klinisch relevanten Konzentrationen [32 bis 1, 024 x MIC (minimale Hemmstoffkonzentration)] durchgeführt. Eine Gesamtgenom Sequenzierung und eine bioinformatische Analyse wurde bei den resistenten Stämmen, die bei diesem Assay entstanden, durchgeführt. Ergebnisse: Durch die Genom Analyse wurden neun Gene antimikrobieller Resistenz (ARGs) bei MDR‐MRSP Isolaten identifiziert, die für die Resistenz gegenüber sieben Antibiotikaklassen verantwortlich waren. Die RFP Aktivität gegenüber den vier Isolaten war konsistent mit einer Zeit‐abhängigen und bakteriostatischen Antwort. Eine RFP Resistenz wurde bei sechs der 28 Time‐Kill Assays beobachtet, dabei handelte es sich um die Konzentrationen 64 x MIC bei MDR‐MRSP1 Isolaten bei 24h, 32 x MIC bei MDR‐MRSP2 bei 48h, 32 x MIC bei MDR‐MRSP3 bei 48h und 256 x MIC bei MDR‐MRSP3 bei 24h. Eine Genom‐weite Mutationsanalyse bei diesen RFP‐resistenten Stämmen enthüllte die verursachenden Mutationen in der Kodierungsregion des rpoB Gens. Schlussfolgerungen und klinische Bedeutung: Eine Studie hat gezeigt, dass 6 mg/kg per os in einer Plasmakonzentration von 600‐1.000 x MIC von S. pseudintermedius resultiert. Basierend auf unseren Daten, sollte diese Dosis eine minimale MIC (x512) erreichen, um die Entstehung einer RFP Resistenz zu verhindern; daher empfehlen wir eine minimale tägliche Dosis von 6 mg/kg für die Behandlung einer MDR‐MRSP Pyodermie, wenn nur limitierte antibiotische Optionen zur Verfügung stehen. 要約: 背景: 犬の Staphylococcus pseudintermedius 由来膿皮症では，抗菌薬耐性が問題となっている。メチシリン耐性および多剤耐性 S. pseudintermedius （MDR‐MRSP）に対してのみリファンピシン（RFP）による治療が検討されている。 仮説・目的: 本研究の目的は、MDR‐MRSP治療においてRFP耐性を誘発しない最適なRFP投与量を決定し，抗菌薬耐性の原因となる変異を特定することであった。 材料と方法: 対照分離株1株およびMDR‐MRSP分離株3株を対象に，臨床的に適切な6濃度（32～1, 024×MIC（最小発育阻止濃度））でTime–kill assay法を実施した。また，Time–kill assay法で得られた耐性株を対象に，全ゲノム再配列決定およびバイオインフォマティクス解析を実施した。 結果: ゲノム解析の結果，MDR‐MRSP分離株には9つの抗菌剤耐性遺伝子（ARG）が同定され，これらは7クラスの抗菌剤に対する耐性を担っていた。4株すべてに対するRFP活性は，時間依存的な静菌反応と一致していた。RFP耐性は28種のTime–kill assayのうち6種で認められ，MDR‐MRSP1株では24時間後に64×MIC，MDR‐MRSP2株では48時間後に32×MIC，MDR‐MRSP3株では48時間後に32×MIC，MDR‐MRSP3株では24時間後に256×MICの濃度であった。 結論と臨床的妥当性: 経口投与6 mg/kgで血漿中濃度が S . pseudintermedius の600～1, 000×MICになるという研究結果がある。我々のデータに基づけば，この用量はRFP耐性発現を防ぐ最小MIC（512×MIC）を達成するはずである。したがって，限られた抗生物質の選択肢しかない場合のMDR‐MRSP膿皮症に対する治療には，1日あたりの最小用量である6 mg/kgを推奨する。 摘要: 背景: 抗生素耐药性是犬假中间型葡萄球菌皮炎中越来越受到关注的问题。利福平(RFP)治疗仅考虑用于耐甲氧西林和多重耐药的假中间型葡萄球菌(MDR‐MRSP)。 假设/目的: 在不会诱导RFP耐药的前提下，确定MDR‐MRSP治疗的最佳RFP剂量，并确定抗菌药物耐药的突变原因。 材料和方法: 在6个临床相关浓度[32‐1, 024×MIC（最小抑菌浓度）]下，针对对照分离株和3株MDR‐MRSP分离株进行时间‐杀灭试验。对本试验开发的耐药菌株进行全基因组重测序和生物信息学分析。 结果: 基因组分析在MDR‐MRSP分离株中鉴定出9个抗菌药物耐药基因(ARGs)，它们是对7类抗生素耐药的原因。全部4株分离株的RFP活性与时间依赖性和抑菌反应一致。28次时间‐杀菌试验中有6次观察到RFP耐药，包括在24h时MDR‐MRSP1分离株的浓度为64×MIC，在48h时MDR‐MRSP2的浓度为32×MIC，48h时MDR‐MRSP3为32×MIC，24h时MDR‐MRSP3为256×MIC。对这些RFP耐药菌株进行全基因组突变分析，发现了rpoB基因编码区是突变原因。 结论和临床相关性: 一项研究表明，6 mg/kg经口给药导致假中间型链球菌的血浆浓度为600‐1, 000×MIC。基于我们的数据，该剂量应达到最小MIC(×512)，以防止发生RFP耐药；因此，当可用的抗生素选择有限时，我们建议MDR‐MRSP脓皮病治疗的最小日剂量为6 mg/kg。 Resumo: Contexto: A resistência a antimicrobianos é uma preocupação crescente na dermatite canina causada por Staphylococcus pseudintermedius. O tratamento com rifampicina (RFP) é apenas considerado em casos de S. pseudintermedius multirresistente e resistente à meticilina (MDR‐MRSP). Hipótese/Objetivos: Determinar a dose ideal de RFP para o tratamento de MDR‐MRSP sem indução de resistência à RFP e identificar as mutações causadoras de resistência a antimicrobianos. Materiais e métodos: Os ensaios de tempo de eliminação ( time‐kill) foram realizados em um isolado controle e três isolados MDR‐MRSP em seis concentrações clinicamente relevantes [32 a 1.024 × MIC (a concentração inibitória mínima)]. O resequenciamento de todo o genoma ( whole‐genome resequencing) e a análise de bioinformática foram realizados nas cepas resistentes desenvolvidas neste ensaio. Resultados: A análise genômica identificou nove genes de resistência antimicrobiana (ARGs) em isolados MDR‐MRSP, que são responsáveis pela resistência a sete classes de antibióticos. A atividade de RFP contra todos os quatro isolados foi consistente com uma resposta bacteriostática tempo‐dependente. A resistência a RFP foi observada em seis dos 28 ensaios time‐kill, incluindo concentrações 64×MIC em isolados MDR‐MRSP1 em 24 h, 32×MIC em MDR‐MRSP2 em 48 h, 32× MIC em MDR‐MRSP3 em 48 h e 256×MIC em MDR‐MRSP3 em 24 h. As análises de mutação em todo o genoma ( whole genome) nessas cepas resistentes a RFP descobriram as mutações causais na região codificadora do gene rpoB . Conclusões e relevância clínica: Um estudo mostrou que 6 mg/kg por via oral resulta em concentrações plasmáticas de 600‐1.000 × MIC de S. pseudintermedius . Com base em nossos dados, esta dose deve atingir o MIC mínimo (×512) para evitar o desenvolvimento de resistência a RFP; portanto, recomendamos uma dose diária mínima de 6 mg/kg para o tratamento de piodermite MDR‐MRSP quando há opções limitadas de antibióticos disponíveis.